Mengukur Efektivitas Representasi: Analisis Dialektika Antara Wakil Rakyat Dan Konstituen Dalam Proses Legislasi - Fredy Rahalus (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
This research aims to analyze and understand the dialectics in the relationship8 between representatives and constituents in the context of Indonesian politics. Within the framework of dialectics, this study explains the contradiction between constituents' expectations and the performance of representatives as a source of change and transformation in the relationship. This research adopts an analytical-descriptive research method where data is collected through literature study or book report. The approach used is a philosophical approach. The research findings indicate that the gap between constituents' expectations and the performance of representatives is a fundamental issue in this relationship. The research identifies several challenges in the relationship between representatives and constituents, including a lack of effective representation, limitations in communication and dialogue, and a lack of accountability of representatives towards constituents. However, through the dialectical approach, the argument of this research emphasizes the importance of building effective communication and dialogue, encouraging active participation of constituents, and improving the accountability of representatives to enhance political representation and responsiveness to the issues faced by constituents. This research contributes to understanding the complex relationship between representatives and constituents and provides insights into the application of dialectical concepts in the context of Indonesian politics. The implications of this research include the need to enhance political understanding and awareness among constituents, strengthen public participation, and foster sustainable relationships between representatives and constituents.